Respostas

2014-08-03T12:30:13-03:00
Olá, Giov1444!

x² + 3x - 6 = -8
x² + 3x - 6 + 8 = 0
x² + 3x + 2 = 0

a = 1
b = 3
c = 2

Δ = b² - 4.a.c
Δ = 3² - 4.1.2
Δ = 9 - 8
Δ = 1

-b +- √Δ / 2.a
-3 +- √1 / 2.1
-3 +- 1 / 2

x' = -3+1/2 = -2/2 = -1
x'' = -3-1/2 = -4/2 = -2
5 4 5
2014-08-03T12:52:56-03:00
X² + 3x - 6 = -8
x² + 3x - 6 + 8 = 0
x² + 3x + 2 = 0

a = 1
b = 3
c = 2

Δ = b² - 4.a.c
Δ = 3² - 4.1.2
Δ = 9 - 8
Δ = 1

-b +- √Δ / 2.a
-3 +- √1 / 2.1
-3 +- 1 / 2

x' = -3+1/2 = -2/2 = -1
x'' = -3-1/2 = -4/2 = -2